(untitled) (Rivista di Psicopatologia Forense, Medicina Legale, Criminologia, 2021)
By the use of profiling and the analysis of the deviant behavioural conduct in general terms, the figure and the behaviour of the drug abuser is examined in his peculiar features as well. In this way a behavioural model reference could rise in those cases in which there is an addicted person or a presumed one. In this paper are also introduced the New Psychoactive Substances (NPS), new drugs that cause important psychological and psychical consequences on individuals who are used to consume them. Therefore, thanks to this focus on familiar, social, environmental and psychopathological causes of the drug abuser, we try to understand his possible relation with criminality and if some initial signals could be identified in order to allow us to recognize an addicted person, introducing in this regard another useful device, the psychographic examination. Finally, also new kind of addictions are here presented together with how they could widen this study, including the particular epidemic situation caused by Covid-19.